David Pareus irénikus hatása a magyar protestáns egyházakra - LUKÁCS, Olga (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
The Irenic Influence of David Pareus over the Hungarian Protestant Churches. The irenical movement was the sum of the ideas propagating the unity of faith of the Protestants and proposing their institutional reunification. The theorist of the 17th century irenical movement was David Pareus (1548–1622), a professor at Heidelberg University. His irenical aspirations are formulated in his work called Irenicum. During the Transylvanian and Hungarian irenical movement (from about 1604 to the early 1630s) a socially and sociologically well-defined group of Reformed preachers, the followers of Pareus, held leadership positions in the Reformed Church, and had a decisive ideological impact on the Transylvanian royal court and the aristocratic circles of Hungary. The union of the two Transylvanian Protestant churches was present as a desire; however, due to historical events the attempts in this respect were unsuccessful.